Parents and children in front of the screen: A television reception studio in Lima - Macassi Lavander, Sandro (1998)
The study of children's television reception and consumption involves considerable complexity, since it is not exhausted in its relationship with the screen, but goes much further. Generally, all spheres that participate in the child's socialization play a decisive role in understanding the complex processes that precede and continue the act of watching television.